Sappanone a prevents diabetic kidney disease by inhibiting kidney inflammation and fibrosis via the NF-κB signaling pathway - Wang, Zhe; Chen, Zhida; Wang, Xinyi; Hu, Yepeng; Kong, Jing; Lai, Jiabin; Li, Tiekun; Hu, Bibi; Zhang, Yikai; Zheng, Xianan; Liu, Xiaoxian; Wang, Shengyao; et al. (Frontiers in Pharmacology, 2022)
Background:Low grade of sterile inflammation plays detrimental roles in the progression of diabetic kidney disease (DKD). Sappanone A (SA), a kind of homoisoflavanone isolated from the heartwood of Caesalpinia sappan, exerts anti-inflammatory effects in acute kidney injury. However, whether SA has beneficial effects on diabetic kidney disease remains further exploration. Methods and Results: In the present study, uninephrectomized male mice were treated with Streptozotocin (STZ, 50 mg/kg) for five consecutive days to induce diabetes. Next, the diabetic mice were administered orally with SA (10, 20, or 30 mg/kg) or vehicle once per day. Our results showed that STZ treatment significantly enhanced damage in the kidney, as indicated by an increased ratio of kidney weight/body weight, elevated serum creatinine and blood urea nitrogen (BUN), as well as increased 24-hour urinary protein excretion, whereas SA-treated mice exhibited a markedly amelioration in these kidney damages. Furthermore, SA attenuated the pathological changes, alleviated fibrotic molecules transforming growth factor-β1 (TGF-β1) and Collagen-IV (Col-IV) production, decreased inflammatory cytokines interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) expression in STZ-treated mice. Similarly, in glomerular mesangial cells, SA pretreatment decreased high glucose (HG)-induced proliferation, inflammatory cytokines excretion and fibrotic molecules expression. Mechanistically, SA decreased the expression of nuclear factor kappa B (NF-κB) and restored the expression of total NF-κB inhibitor alpha (IκBα) both in vivo and in vitro. Conclusion: Our data suggest that SA may prevent diabetes-induced kidney inflammation and fibrosis by inhibiting the NF-κB pathway. Hence, SA can be potential and specific therapeutic value in DKD.